PERSEPSI ORANG TUA MURID TERHADAP MANFAAT KEGIATAN EKSTRAKURIKULER FUTSAL PUTRI DI SMA - Sukma, Deddy; Hidasari, Fitriana Puspa; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractParents' perception of students against the benefits of futsal extracurricular activities in Pontianak high school. The method in this study uses quantitative descriptive, with a survey form. the population in this study were all parents of futsal female extracurricular members in 3 schools (Santun Untan High School, SMA N 7, SMA N 8) with a total of 60 people. the sample in this study were 60 students. Consists of 20 members of women's futsal extracurricular activities. Consisting of 20 members of women's futsal extracurricular activities SMA Santun untan students for 20 students, SMA N 7 for 20 students, SMA N 8 for 20 students determination of samples based on data and recommendations from sports teachers who train extracurricular activities. Based on the results of data analysis obtained parents' perceptions of female futsal extracurricular activities in high school, Santun untan high school, SMA N 7 and SMA N 8. Obtained parents' perceptions with very good categories of 2%, both 32%, enough 37%, less 23% and not good 7%. This means that parents' perceptions of the benefits of women's futsal extracurricular activities in high schools are quite sufficient with a percentage of 37%. The average perception of parents with a score of 81 is in the sufficient category.Â Keywords: Perception of Parents, Extracurricular, Futsal